Joint species distribution modelling : with applications in R - Ovaskainen, Otso; Abrego, Nerea (Ecology, biodiversity and conservation, 2020)
"Joint Species Distribution Modelling (JSDM) is a fastdeveloping field and promises to revolutionise how data on ecological communities are analysed and interpreted. Written for both readers with a limited statistical background, and those with statistical expertise, this book provides a comprehensive account of JSDM. It enables readers to integrate data on species abundances, environmental covariates, species traits, phylogenetic relationships, and the spatio-temporal context in which the data have been acquired. Step-by-step coverage of the full technical detail of statistical methods is provided, as well as advice on interpreting results of statistical analyses in the broader context of modern community ecology theory. With the advantage of numerous example R-scripts, this is an ideal guide to help graduate students and researchers learn how to conduct and interpret statistical analyses in practice with the R package HMSC-R, providing a fast starting point for applying joint species distribution modelling to their own data"--
Keywords: Biogeography : Statistical methods; Ecology : Statistical methods; R (Computer program language); eliömaantiede; ekologia; R-kieli; ohjelmointikielet; tilastomenetelmät